2017
DOI: 10.1007/s10086-017-1632-5
|View full text |Cite
|
Sign up to set email alerts
|

Plywood made from plasma-treated veneers: melamine uptake, dimensional stability, and mechanical properties

Abstract: This study investigates the dimensional stability and mechanical properties of plywood boards made of thermally modified and unmodified beech veneers that have undergone plasma pre-treatment before melamine resin impregnation. The water and melamine resin uptake and resulting weight percent gain of the veneers were investigated, whereby the air plasma pre-treated veneers showed improved liquid uptake. Five-layer plywood boards were then manufactured and tested for their dimensional stability, compressive stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The effects of low-temperature plasma treatment’s influence on wood and wood-based products have been investigated more recently. Altgen et al and Wascher et al showed that the physicomechanical properties of plywood and fiberboards improved after a plasma treatment of the base wood material [ 14 , 15 ]. Investigations of plasma treatments of injection-molded and/or extruded alkene-based WPCs by Oporto et al and Hünnekens et al revealed a better wettability and additionally Hünnekens et al showed a recombination of the surface and therefore a time-dependent reduction in the surface activation effect [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of low-temperature plasma treatment’s influence on wood and wood-based products have been investigated more recently. Altgen et al and Wascher et al showed that the physicomechanical properties of plywood and fiberboards improved after a plasma treatment of the base wood material [ 14 , 15 ]. Investigations of plasma treatments of injection-molded and/or extruded alkene-based WPCs by Oporto et al and Hünnekens et al revealed a better wettability and additionally Hünnekens et al showed a recombination of the surface and therefore a time-dependent reduction in the surface activation effect [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to provide a concrete reference to the previously discussed and published studies [9,13], native and thermally modified beech veneers and melamine resin were used in this study. In the context of this study, the term "reference" is used exclusively for the plywood specimens made from non-plasma-pretreated beech veneers, where these veneers remained in the immersion bath until a liquid uptake or WPG (WPG = Weight Percentage Gain) of plasma-pretreated veneers (1 s impregnation time) was achieved.…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, plywood samples made from beech veneers treated with plasma and subsequently impregnated with melamine resin showed higher shear strength than the reference [13]. Recent studies [9,13,14] on the comparability of plywood samples made from plasma-pretreated and non-pretreated beech veneers raise the following question: how do plywood specimens perform with respect to dimensional stability and mechanical properties when the individual (non-plasma-pretreated) veneers of these specimens have the same melamine resin uptake-with a correspondingly longer immersion time-as the plywood made from plasma-pretreated veneers (impregnation time 1 s)? Although this question has already been briefly touched upon in Reference [13], there is a lack of systematic investigation and discussion on this issue.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In general, plasma technology is used with woodbased biomaterials to enhance gluing, composites, and coatings (Ž igon et al 2018). Plasma pretreatments were shown to improve adhesion strengths (Král et al 2015;Ž igon et al 2020a), while reducing susceptibility to humidity (Avramidis et al 2010;Wascher et al 2017) and weathering (Ž igon et al 2018). Further, plasma treatments can deposit functional coatings, such as super-hydrophobic, super-hydrophilic, or photocatalytic functional layers (Podgorski et al 2001;Mai and Militz 2004;Wallenhorst et al 2018).…”
Section: Introductionmentioning
confidence: 99%